A randomized, double-blind comparison of OROS(® )hydromorphone and controlled-release morphine for the control of chronic cancer pain - Hanna, Magdi (BioMed Central, 2008)
BACKGROUND: Long-acting opioid formulations are advocated for maintaining pain control in chronic cancer pain. OROS(® )hydromorphone is a sustained-release formulation of hydromorphone that requires dosing once daily to maintain therapeutic concentrations. The objective of this study was to demonstrate the clinical equivalence of immediate-release and sustained-release formulations of hydromorphone and morphine for chronic cancer pain. METHODS: 200 patients with cancer pain (requiring ≤ 540 mg/d of oral morphine) participated in this double-blind, parallel-group trial. Patients were randomized to receive hydromorphone or morphine (immediate-release for 2–9 days, sustained-release for 10–15 days). Efficacy was assessed with the Brief Pain Inventory (BPI), investigator and patient global evaluations, Eastern Cooperative Oncology Group performance status, and the Mini-Mental State Examination. The primary endpoint was the 'worst pain in the past 24 hours' item of the BPI, in both the immediate-release and sustained-release study phases, with treatments deemed equivalent if the 95% confidence intervals (CI) of the between-group differences at endpoint were between -1.5 and 1.5. No equivalence limits were defined for secondary endpoints. RESULTS: Least-squares mean differences (95% CI) between groups were 0.2 (-0.4, 0.9) in the immediate-release phase and -0.8 (-1.6, -0.01) in the sustained-release phase (intent-to-treat population), indicating that the immediate-release formulations met the pre-specified equivalence criteria, but that the lower limit of the 95% CI (-1.6) was outside the boundary (-1.5) for the sustained-release formulations. BPI 'pain now PM' was significantly lower with OROS(® )hydromorphone compared with controlled-release morphine (least-squares mean difference [95% CI], -0.77 [-1.49, -0.05]; p = 0.0372). Scores for other secondary efficacy variables were similar between the two sustained-release treatments. At endpoint, > 70% of investigators and patients rated both treatments as good to excellent. The safety profiles of hydromorphone and morphine were similar and typical of opioid analgesics. CONCLUSION: Equivalence was demonstrated for immediate-release formulations of hydromorphone and morphine, but not for the sustained-release formulations of OROS(® )hydromorphone and controlled-release morphine. The direction of the mean difference between the treatments (-0.8) and the out-of-range lower limit of the 95% CI (-1.6) were in favor of OROS(® )hydromorphone. TRIAL REGISTRATION: ClinicalTrials.gov: NCT0041054